Prototype of Temperature and Humidity Control System in Dry House or Coffee Drying Dom Using NodeMCU ESP8266 - Zaky, Naufal; Basri, Mhd (Ilmu Bersama Center, 2025)
Coffee is a very popular plant in the world as a raw material that has a distinctive taste and aroma. One of the most important post-harvest stages is the drying of coffee beans, because it can affect the quality of coffee beans so that the bargaining value of coffee prices can increase. Farmers in general still do drying traditionally by drying coffee beans in an open room. IoT currently provides the ability to connect various devices and sensors in a centralized network. as an advantage of IoT technology, it provides a solution for the owner of the temperature and humidity control system in the coffee warehouse to monitor the temperature and humidity in the coffee warehouse directly or remotely. This study aims to develop a prototype of a temperature and humidity control system in a dry house for coffee drying dom that can be viewed remotely via a smartphone and can be seen directly through the tools that have been designed. The DHT22 sensor is used to detect air temperature and humidity conditions. This temperature detection process will be active if the read temperature conditions exceed normal limits. The IoT platform as a process of sending data and reading data on this system uses the Blynk application. The result of this research is the design of a temperature and humidity control system in a coffee warehouse using a DHT22 sensor that works according to what has been programmed on the NodeMCU ESP8266 so that it can see the temperature and humidity of the air through the Blynk application on a smartphone and the system can work automatically so that when the temperature is above 34 ° C the system raises a warning sign on the device that has been designed and raises a notification on the Blynk application. Dry house is an important building in coffee processing to maintain the quality of coffee beans during the drying process. In this research, we design and implement an automatic system that uses microcontroller-based temperature and humidity sensors to control environmental conditions in the dry house. The development method includes analyzing system requirements, designing hardware and software, and testing the system to verify its performance and reliability. The results show that the developed prototype is able to maintain temperature and humidity within the optimal range during the coffee drying process, which is expected to improve efficiency and quality of the final product. The practical implication of this research is the development of technology that can be applied in the coffee processing industry to improve process control and reduce yield loss due to uncontrolled environmental changes.